HALAL COSMETICS REPURCHASE INTENTION: THE ROLE OF MARKETING IN SOCIAL MEDIA - Mohamad Isa Abd Jalil; Suddin Lada; Mohd Ashari Bakri; Zakiah Hassan (Bank Indonesia, 2021)
This research aims to study the effects of social media marketing strategies on the repurchase intention among buyers of halal cosmetics manufactured in Malaysia. The study, based on the theory of social media marketing, identifies the nexus, and considers the mediating functions of word-of-mouth brand recognition and electronic word-of-mouth communication (e-WOM). The work takes a holistic view of brand recognition and e-WOM with reference to the two main relations, social media marketing strategy and repurchasing intention. The partial least squares structural equation modelling (PLS-SEM) method was employed and data collected from 300 respondents (followers) via an online questionnaire. The results indicate that there is a significant influence of social media marketing (SMM) on repurchase intention, brand awareness, and e-WOM; the impact is higher on brand awareness, followed by repurchase intention and eWOM. These results demonstrate that efficient brand management of the use of social media platforms will help increase brand awareness among halal cosmetics buyers. When used correctly, SMM may assist the distribution and communication of the most up-to-date information on cosmetic products and brands, resulting in increased awareness and repurchase intent. At the same time, eWOM is a useful tool for their respective followers to disseminate information to followers. The research has important implications for the halal cosmetics sector, as it contributes to the theoretical and management literature on social media marketing strategy.